Akurasi fibrinogen dan hs-crp sebagai biomarker pada sindrom koroner akut (SKA) - Djanggan Sargowo (Jurnal Kardiologi Indonesia, 2014)
Background: acute coronary syndrome (ACS) refers to any group of clinical symptom compatible with acute myocardial infarction (AMI). AMI is a major cause of death and disability worldwide with the greates risk of death within the first hours of AMI onset. Thus, the identification of novel biomarkers that improve current strategies and/or accurately identify subjects who are at risk of developing acute and chronic manifestation of cardiovascuar disease are desperately needed.Obsjective: this study was aimed to determine the accuracy diagnostic value of Fibrinogen and High Sensitivity C-Reactive Protein as a biomarker for Acute Coronary SyndromeSubjects and methods: an observational study with cross sectional approach, was conducted from February to July 2011 involving 76 male and female patients aged 35 to 80 years old for cases all well as controls. The biomarker measured were level of Fibrinogen and Hs-CRP. We used Receiver Operating Curve to determine the cut off test. We calculated of sensitivity, specificity, likelihood ratio, negative predictive value, and postive predictive value for biomarkers in combination and single.Results : the mean age in both groups was 57.5 year old. Level of the Fibrinogen in cases (5.8±1.56) was significantly different than control (3.78±1.78). concentration Hs-CRP in cases (4.04±1.94) was significantly different than control (1.98±1.25). both these biomarkers can be used as a diagnostic tool for Acute Coronary Syndrome in combination or single.Conclusion : the combination of Fibrinogen and Hs-CRP has the better diagnostic value that when used single.